Tirta Baruna Symbolization in the Javanese Philosophy of Leadership Characters: The Leadership of Sultan Hadiwijaya - Suryo Ediyono (Javanologi: International Journal of Javanese Studies, 2023)
Baruno is one of the most complex leadership philosophies in Hasta Brata that exist today, because Javanese philosophy has several advantages as a concept of leadership. Samudra as a symbol of leadership character with oceanic properties are able to receive water from any river, either dirty or clean water and then process all the water content of the river in the water depth. Baruna are the noble qualities of the universe according to Javanese philosophy, can be a guide for every leader. This research is a case study of character Sultan Hadiwijaya using the historical method, which includes: (1) Heuristic, namely, activity preparing stable-traces of the past (2) Criticism of history, namely investigating whether traces of it true, both form and content (3) Interpretation, namely establishing the interconnected meanings of the facts obtained. Sultan Hadiwijaya is a Pajang leader who have eyes and mind widely. Accepting opinions from around as a sign of a leader's respect for others. Leaders do not swallow the input that comes, but think carefully all the opinions that exist, leaders are able to gain new knowledge from the surrounding. An ideal leader, ie (1) extensive knowledge, (2) good skills, and (3) Attitude or moral praise.